Bacterial Cell Surface Display of a Multifunctional Cellulolytic Enzyme Screened from a Bovine Rumen Metagenomic Resource - Ko, Kyong-Cheol; Lee, Binna; Cheong, Dae-Eun; Han, Yunjon; Choi, Jong Hyun; Song, Jae Jun (Journal of microbiology and biotechnology, 2015)
A cell surface display system for heterologous expression of the multifunctional cellulase, CelEx-BR12, in Escherichia coli was developed using truncated E. coli outer membrane protein C (OmpC) as an anchor motif. Cell surface expression of CelEx-BR12 cellulase in E. coli harboring OmpC-fused CelEx-BR12, designated MC4100 (pTOCBR12), was confirmed by fluorescence-activated cell sorting and analysis of outer membrane fractions by western blotting, which verified the expected molecular mass of OmpC-fused CelEx-BR12 (~72 kDa). Functional evidence for exocellulase activity was provided by enzymatic assays of whole cells and outer membrane protein fractions from E. coli MC4100 (pTOCBR12). The stability of E. coli MC4100 (pTOCBR12) cellulase activity was tested by carrying out repeated reaction cycles, which demonstrated the reusability of recombinant cells. Finally, we showed that recombinant E. coli cells displaying the CelEx-BR12 enzyme on the cell surface were capable of growth using carboxymethyl cellulose as the sole carbon source.